2016
DOI: 10.1038/mp.2016.3
|View full text |Cite
|
Sign up to set email alerts
|

A meta-analysis of blood cytokine network alterations in psychiatric patients: comparisons between schizophrenia, bipolar disorder and depression

Abstract: Schizophrenia, bipolar disorder and major depressive disorder (MDD) have all been associated with aberrant blood cytokine levels; however, neither the pattern of cytokine alterations nor the impact of clinical status have been compared across disorders. We performed a meta-analysis of blood cytokines in acutely and chronically ill patients with these major psychiatric disorders. Articles were identified by searching the PubMed, PsycInfo and Web of Science, and the reference lists of these studies. Sixty-eight … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

62
1,051
6
22

Year Published

2016
2016
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 1,362 publications
(1,141 citation statements)
references
References 157 publications
62
1,051
6
22
Order By: Relevance
“…Indeed, recent studies have indicated that high inflammation (plasma CRP concentrations 43 mg/l, as defined by the American Heart Association; Ridker, 2003) is consistently found in 20-40% of patients with MDD, with higher concentrations observed in patients who are resistant to standard antidepressant therapies Haroon et al, 2016;Raison et al, 2013a;Raison et al, 2013b;Rapaport et al, 2016). Similar increases in inflammatory cytokines and acute-phase reactants have also been reported in patients with bipolar disorder and schizophrenia, including meta-analyses (Goldsmith et al, 2016b;Miller et al, 2011;Potvin et al, 2008). Increased inflammatory cytokine concentrations in the cerebrospinal fluid (CSF) of patients with unipolar and bipolar depression, and schizophrenia have also been observed (Garver et al, 2003;Levine et al, 1999;Schwieler et al, 2015;Soderlund et al, 2011;Soderlund et al, 2009).…”
Section: Increased Inflammation In Psychiatric Disordersmentioning
confidence: 84%
See 1 more Smart Citation
“…Indeed, recent studies have indicated that high inflammation (plasma CRP concentrations 43 mg/l, as defined by the American Heart Association; Ridker, 2003) is consistently found in 20-40% of patients with MDD, with higher concentrations observed in patients who are resistant to standard antidepressant therapies Haroon et al, 2016;Raison et al, 2013a;Raison et al, 2013b;Rapaport et al, 2016). Similar increases in inflammatory cytokines and acute-phase reactants have also been reported in patients with bipolar disorder and schizophrenia, including meta-analyses (Goldsmith et al, 2016b;Miller et al, 2011;Potvin et al, 2008). Increased inflammatory cytokine concentrations in the cerebrospinal fluid (CSF) of patients with unipolar and bipolar depression, and schizophrenia have also been observed (Garver et al, 2003;Levine et al, 1999;Schwieler et al, 2015;Soderlund et al, 2011;Soderlund et al, 2009).…”
Section: Increased Inflammation In Psychiatric Disordersmentioning
confidence: 84%
“…A significant proportion of patients with psychiatric disorders exhibit a chronic, low-grade inflammation, as measured by increased peripheral and central inflammatory cytokines, inflammatory mediators, and acute-phase reactants (for review, see Barbosa et al, 2014, Felger and Lotrich, 2013b, Goldsmith et al, 2016band Haroon et al, 2012. Findings from numerous laboratories have consistently indicated that innate immune activation and the release of inflammatory cytokines preferentially affect reward circuitry and basal ganglia DA to contribute to reduced motivation and motor slowing (Brydon et al, 2008;Capuron et al, 2007;Capuron et al, 2012;Eisenberger et al, 2010;Felger and Miller, 2012;Harrison et al, 2015b;Majer et al, 2008).…”
Section: Introductionmentioning
confidence: 99%
“…IL-6 is a key component of the inflammatory response in the brain, a profound stimulator of acute phase proteins from the liver and has been implicated in the etiology of neuropsychiatric disorders such as depression (Dowlati et al, 2010;Howren et al, 2009;Miller and Raison, 2016;Valkanova et al, 2013) and schizophrenia (Goldsmith et al, 2016). IL-6 has mixed effects on the glutamate system attributable to the more chronic and nuanced nature of its effects.…”
Section: Il-6mentioning
confidence: 99%
“…Nevertheless, when an immune challenge becomes chronic or unregulated, as occurs in patients who are receiving chronic cytokine treatments or those exposed to chronic medical illness or psychological stress, the cytokines may contribute to the development of clinically relevant behavioral symptoms and neuropsychiatric diseases, including major depression (Raison and Miller, 2013). In support of this hypothesis, depressive symptoms have been shown to be associated with increased serum and plasma concentrations of TNF, IL-6 and C-reactive protein (Dowlati et al, 2010;Goldsmith et al, 2016;Strawbridge et al, 2015;Valkanova et al, 2013). Most importantly, recent longitudinal studies have extended these cross-sectional observations by reporting that increased inflammatory markers in non-depressed individuals predict the later development of major depression (Gimeno et al, 2009;Pasco et al, 2010;van den Biggelaar et al, 2007).…”
Section: Introductionmentioning
confidence: 98%